Preparing the spatial signature map of the solar energy farms in Dhi Qar Governorate using GIS - Al-Rikabi, Ass. Pro PhD Hamed Sfeih Ajrash (Thi Qar Arts Journal, 2022)
At the present time, the world is exposed to many problems related to obtaining energy sources. Therefore, man is always looking for new and inexhaustible sources of energy to cover his increasing needs. Many energy sources are defective in their depletion, the high cost of their exploitation, and the negative impact of their use on the environment, and man has alerted in the modern era. To the possibility of benefiting from the heat of the sun's rays, which is characterized as clean, renewable, permanent and inexhaustible energy. As a result of the significant increase in the consumption of electric energy in Iraq and in the study area (Thi Qar governorate) in particular, the power generation facility was introduced and some of it destroyed during the previous years had affected the infrastructure services network, including electric power plants, transmission lines and energy supply, and in order to provide a source Safe energy and a quick solution to the energy problem requires providing economically feasible alternatives, including (electrical solar energy farms) It is necessary to rely on a method that is compatible with the nature of the subject, and for that, the cartographic, descriptive and quantitative method has been relied upon to present and analyze the natural characteristics and uses of the land in the area that can be served by electric farms. In order to apply this renewable technology.